2023
DOI: 10.3390/ijerph20043338
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Victimization of School Bullies Affect Core Self-Evaluations in Young Adulthood? A Moderated Mediation Model

Abstract: Early victimization is associated with a range of psychological adaptation problems in young adulthood, including core self-evaluations. However, little is known about the mechanisms underlying the association between early victimization and young adults’ core self-evaluations. This study examined the mediating role of negative cognitive processing bias and the moderating role of resilience in the relationship. A total of 972 college students were recruited to complete measures of early victimization, negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Although all of the above evidence suggests that interpersonal adjustment is a signi cant predictor of college student depression, the effect of college student interpersonal adjustment on college student depression is not simple and direct. Wang' (2023) work showed that core self-evaluation is an essential mediating variable in explaining how other factors in uence individual adjustment [25]. Deng (2019) found that low levels of core self-evaluation, a cognitive factor that exacerbates susceptibility to depression, predisposes to depression [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although all of the above evidence suggests that interpersonal adjustment is a signi cant predictor of college student depression, the effect of college student interpersonal adjustment on college student depression is not simple and direct. Wang' (2023) work showed that core self-evaluation is an essential mediating variable in explaining how other factors in uence individual adjustment [25]. Deng (2019) found that low levels of core self-evaluation, a cognitive factor that exacerbates susceptibility to depression, predisposes to depression [26].…”
Section: Introductionmentioning
confidence: 99%